2013
DOI: 10.1210/jc.2013-1777
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Women With Uterine Leiomyomas

Abstract: Vitamin D is an emerging regulator of uterine leiomyoma development. Cohort and interventional studies are pressingly needed to confirm a causal relationship and to investigate the potential therapeutic benefits of vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
110
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 19 publications
20
110
0
10
Order By: Relevance
“…The Al-Hendy group first reported on the association between lower serum vitamin D levels and increased susceptibility to uterine fibroids in 2012 in a cohort of black and white women in North Africa (138,139). This was followed by two other major studies including a cohort of women from the eastern United States in 2013 by Baird and colleagues (140) and another cohort of Italian women in 2013 by Paffoni and colleagues (141). The high prevalence of vitamin D deficiency in African Americans may explain, at least in part, the high prevalence of uterine fibroids in this patient population (142).…”
Section: Vitamin D Signalingmentioning
confidence: 97%
“…The Al-Hendy group first reported on the association between lower serum vitamin D levels and increased susceptibility to uterine fibroids in 2012 in a cohort of black and white women in North Africa (138,139). This was followed by two other major studies including a cohort of women from the eastern United States in 2013 by Baird and colleagues (140) and another cohort of Italian women in 2013 by Paffoni and colleagues (141). The high prevalence of vitamin D deficiency in African Americans may explain, at least in part, the high prevalence of uterine fibroids in this patient population (142).…”
Section: Vitamin D Signalingmentioning
confidence: 97%
“…These findings were supported by Baird et al when they determine that women with sufficient levels of vitamin D were less likely to develop uterine fibroids and found that levels of vitamin D was 10% of African-Americans and 50% of Caucasians, with an adjusted odds ratio of 0.68 [25]. Also, Paffoni et al found that women with vitamin D deficiency were more likely to have uterine fibroids, with an adjusted odds ratio of 2.4 [26].…”
Section: Vitamin D and Uterine Fibroidsmentioning
confidence: 73%
“…Baird et al addressed that women with uterine leiomyomas have lower levels of serum vitamin D3 compared to their healthy counterpart women [25]. Moreover, serum levels of vitamin D3 are inversely proportional to leiomyoma sizes, supporting that vitamin D3 deficiency could be a potential risk factor for the development of uterine leiomyoma [26].…”
Section: Vitamin D and Uterine Fibroidsmentioning
confidence: 99%
“…Kobiety z prawidłowym stężeniem 25(OH)D w surowicy ryzyko rozwoju mięśniaków było o 32% mniejsze niż u kobiet z deficytem 25(OH)D [32].…”
Section: Mięśniakiunclassified